Academic Challenges and Success Strategies of International Medical Students in a Private Medical Institution in Malaysia: A Conceptual Analysis - Puvaneswaren, Parmasivam; Omar, Rosmaria; Mahmood, Rosinah; Abdul Malik, Mahani; Kanakesvary, Poongavanam; Nithyavani, Manikam (Jurnal Pendidikan Bitara UPSI, 2025)
Background: As Malaysia positions itself as a regional hub for international medical education, understanding the academic experiences of international students in private medical schools has become increasingly critical. While existing literature addresses general challenges faced by international students, limited research specifically examines the unique academic, cognitive, and social challenges encountered by international medical students pursuing high-stakes medical degrees. Theoretical Framework: This study employs an integrated theoretical approach combining Bronfenbrenner’s Ecological Systems Theory and Tinto’s Theory of Student Retention to examine student experiences from multiple perspectives, contextualizing academic integration within both institutional and broader ecological systems that influence learning and adaptation. Purpose: This conceptual analysis aims to explore the multifaceted academic challenges faced by international medical students, moving beyond traditional language and cultural adjustment issues to examine cognitive preparedness differences that may impact academic performance and retention. Key Findings: The analysis reveals that academic challenges extend beyond conventional adaptation issues, suggesting that international medical students may exhibit inherent differences in cognitive preparedness that significantly influence their academic success. These findings highlight the need for more responsive institutional frameworks that align pedagogical approaches with diverse student readiness levels. Implications: The study advocates for culturally and cognitively inclusive educational practices that promote meaningful academic integration. Recommendations include developing adaptive teaching methodologies and support systems tailored to the diverse cognitive and cultural backgrounds of international medical students. Conclusion: This research contributes to the broader discourse on educational internationalization by providing actionable insights for educators and policymakers to enhance student retention and create sustainable, student-centered learning environments in Malaysian medical education.